2016
DOI: 10.1016/j.matbio.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Makings of a brittle bone: Unexpected lessons from a low protein diet study of a mouse OI model

Abstract: Glycine substitutions in type I collagen appear to cause osteogenesis imperfecta (OI) by disrupting folding of the triple helix, the structure of which requires Gly in every third position. It is less clear, however, whether the resulting bone malformations and fragility are caused by effects of intracellular accumulation of misfolded collagen on differentiation and function of osteoblasts, effects of secreted misfolded collagen on the function of bone matrix, or both. Here we describe a study originally conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 38 publications
(67 reference statements)
0
22
0
Order By: Relevance
“…We tested whether enhancing Beclin 1-Vps34-UVRAG had an effect similar to that of Raptor haploinsufficiency on MPS chondrocytes both in vitro and in vivo. Tat-Beclin 1, but not a mutated version, rescued endosomal PI3P levels ( Figure 5, A and B) and in turn normalized the autophagic flux in Gusb-KO chondrocytes, as demonstrated by bly, recent findings showed that feeding mice a low-protein diet that induces autophagy reduced the intracellular accumulation of misfolded collagen in osteoblasts and improved bone matrix mineralization in a mouse model of osteogenesis imperfecta (39). Taken together, these observations suggest that the modulation of autophagy may represent a possible therapeutic approach for the treatment of skeletal disorders that are associated with defective collagen trafficking and secretion.…”
Section: Gfp-lc3mentioning
confidence: 70%
“…We tested whether enhancing Beclin 1-Vps34-UVRAG had an effect similar to that of Raptor haploinsufficiency on MPS chondrocytes both in vitro and in vivo. Tat-Beclin 1, but not a mutated version, rescued endosomal PI3P levels ( Figure 5, A and B) and in turn normalized the autophagic flux in Gusb-KO chondrocytes, as demonstrated by bly, recent findings showed that feeding mice a low-protein diet that induces autophagy reduced the intracellular accumulation of misfolded collagen in osteoblasts and improved bone matrix mineralization in a mouse model of osteogenesis imperfecta (39). Taken together, these observations suggest that the modulation of autophagy may represent a possible therapeutic approach for the treatment of skeletal disorders that are associated with defective collagen trafficking and secretion.…”
Section: Gfp-lc3mentioning
confidence: 70%
“…11 Rapamycin-treated WT mice had normal body weight and long bone length, and the improvement in trabecular bone structure with rapamycin treatment is consistent with the concept that an autophagy-inducing low-protein diet may improve osteoblast differentiation and/or bone mineralization. 10 Recent studies have similarly shown that autophagy promotes osteogenic differentiation of human bone marrow mesenchymal stem cells 32 and osteoblast-specific ablation of autophagy in mice results in reduced bone mass. 33 Moreover, in several mouse or rat models of osteopenia, rapamycin treatment was beneficial, 20,22 suggesting possible therapeutic applications in some bone loss conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is reasonable to hypothesize that therapeutic induction of autophagic degradation of the intracellularly retained mutant misfolded collagens should ameliorate the ER stress and deleterious downstream consequences on osteoblast differentiation and function in vivo. Preliminary testing of this approach used autophagy stimulation by a low‐protein diet in the OI mice . While this resulted in some beneficial effect on osteoblast differentiation and mineralization, the diet significantly reduced both WT and OI mouse growth, preventing any conclusions on the therapeutic effects on OI mouse bone.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,14 An imbalance on the amounts and distribution of the bone matrix components (eg, HA crystals and collagen fibers) can lead to serious pathologic alterations on bone microarchitecture and composition, compromising its mechanical properties. These alterations are commonly associated with increased risk of fracture, as described in several bone pathologies related to impaired mineralization of the bone matrix, such in osteogenesis imperfecta, 15 osteomalacia, and rickets. 16,17 Moreover, denser bones do not necessarily translate into stronger bones and resistance to fracture.…”
Section: Introductionmentioning
confidence: 99%